Development of Secure API to Support ICD-10 Based Electronic Medical Records Interoperability - Wijayakusuma, I Gusti Ngurah Lanang; Sudarma, Made; Putra, I Ketut Gede Darma; Sudana, Oka; Jo, Minho; Gautama, I Putu Winada (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2025)
Previous research in 2021 and 2022 has yielded a revolutionary health examination system. This system seamlessly integrates the World Health Organization's International Classification of Diseases-10 (ICD-10) data, ensuring diagnoses align with global standards and thereby enhancing the quality of healthcare provision. A pivotal achievement is the creation of a sophisticated doctor's examination interface, designed for precision and efficiency. Complementing this interface, a search engine autonomously generates relevant keywords, successfully passing the rigorous black-box test, which attests to its robustness and reliability in retrieving critical medical information. A new challenge arises in enabling seamless access to the stored medical record data for various stakeholders, including the Ministry of Health, BPJS, insurance companies, and other relevant entities. To address this, the research team has devised the Application Programming Interface (API). Functioning as a crucial bridge, this API facilitates interoperability among diverse systems. Adherence to the stringent security standards set by the Open Web Application Security Project (OWASP) ensures that the exchange of medical data occurs within a secure environment. Consequently, sensitive patient information can be shared across platforms without compromising confidentiality or integrity.